2003
DOI: 10.1037/0022-0167.50.2.252
|View full text |Cite
|
Sign up to set email alerts
|

Race and sex effects on attitudinal perceptions of acquaintance rape.

Abstract: In an examination of sex and race effects on attitudes about sexual assault, 336 Latino and Caucasian undergraduates reacted to a written acquaintance rape vignette that manipulated victim and perpetrator race. Reactions were assessed by the Rape Empathy Scale, the Attitudes Toward Rape Victim Scale (ARVS), and the Rape Myth Acceptance Scale (RMAS). Results indicated that women reported higher perceptions of empathy, ascribed more credibility toward the rape victim, and were less accepting of rape myths compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 23 publications
10
86
1
3
Order By: Relevance
“…Rape victim empathy has also been shown to be negatively related to rape myth acceptance (Forbes, Adams-Curtis, Pakalka, & White, 2006;Gerger et al, 2007;Jimenez & Abreu, 2003;Mason et al, 2004;Miller et al, 2011). Likewise, people with rape experience were proven to be more empathetic towards a victim than those without personal victimization (Osman, 2011(Osman, , 2014Smith & Frieze, 2003).…”
Section: Rape Empathymentioning
confidence: 98%
See 1 more Smart Citation
“…Rape victim empathy has also been shown to be negatively related to rape myth acceptance (Forbes, Adams-Curtis, Pakalka, & White, 2006;Gerger et al, 2007;Jimenez & Abreu, 2003;Mason et al, 2004;Miller et al, 2011). Likewise, people with rape experience were proven to be more empathetic towards a victim than those without personal victimization (Osman, 2011(Osman, , 2014Smith & Frieze, 2003).…”
Section: Rape Empathymentioning
confidence: 98%
“…Osman (2014 further reported that victimized women are more empathetic in acquaintance rape (but not in stranger rape). Jimenez and Abreu (2003) explored gender and race (European American couple, Latino couple, an interracial couple composed of a Latino and an European American woman, and an interracial couple composed of a Latina and an European American man) effects on perceptions of acquaintance rape (using a sample composed of Latino and European American undergraduates). The dependent variables were rape empathy, attitudes towards rape victim, and rape myth acceptance.…”
Section: Rape Empathymentioning
confidence: 99%
“…Mais concretamente, os estudos revelam que os homens concordam mais com mitos sobre a violação do que as mulheres (Brady et al, 1991;Davies, Pollard, & Archer, 2001;Geiger, Fisher, & Eshet, 2004;Hinck & Thomas, 1999), culpam mais as vítimas (White & Kurpius, 2002) e sustentam atitudes menos tolerantes face às mesmas (Jiminez & Abreu, 2003;Nagel, Matsuo, McIntyre, & Morrison, 2005;William & Pollard, 2003). Autores como Doherty e Anderson (1998) concluem que tal realidade decorre "da natureza altamente genderizada da violação e das expectativas culturais que norteiam as relações sexuais e suas transgressões" (p. 229).…”
Section: Fundamentação Teóricaunclassified
“…The results obtained are contrary to the results obtained by researches carried out in the past (eg. Jiminez & Abreu [37]). However, these results may have been obtained because of the fact that more restrictions are placed on women and they are consistently taught to be more traditional than men in our society.…”
Section: Discussionmentioning
confidence: 99%